南極望遠鏡計画 - 中井, 直正; 市川, 隆; 瀬田, 益道; 本山, 秀明; 宮岡, 宏; 他南極天文, コンソーシアム; NAKAI, Naomasa; ICHIKAWA, Takashi; SETA, Masumichi; MOTOYAMA, Hideaki; MIYAOKA, Hiroshi; Consortiaum, of Antarctica Astronomy (2013)
(New) Dome Fuji Station, which is located at 3800m above sea level and whose temperature is quite low (-20℃～-80℃), is one of the best and unique sites for astronomical observations at infrared to submillimeter wavelengths on the ground. We are planning to constract two large terahertz and infrared telescopes at the station under the 9th JARE six-year plan, aiming at making astronomical observations including to search missing galaxies. 第4回極域科学シンポジウム 特別セッション：[S] 南極研究の将来展望―第Ⅸ期6か年計画策定に向けて 11月14日（木） 国立極地研究所 ２階大会議室 conference object